PREVALENCE OF MYCOTOXINS IN POULTRY FEEDS AND FEED INGRIEDENTS IN PUNJAB (PAKISTAN) - M. A. Anjum; A; W; Sahota; M. Akram; I. Ali (Journal of Animal and Plant Sciences, 2011)
A total of 100 samples, 50 each of layer starter and broiler starter feeds manufactured by 10 different commercial feed mills were collected to assess contamination of aflatoxin B2 and Ochratoxin A in poultry feeds and feed ingredients in Punjab. 440 samples of different poultry feed ingredients including cereal grains and animal and vegetable protein sources were also collected from all over Punjab and were analyzed for Ochratoxin A (OA) content. The mean concentration of aflatoxin B2 in layer and broiler starter rations was observed to range from 10.80 (+2.16) to 39.20 (+3.67) µg Kg1. .Out of 100 feed samples tested, 40 contained higher than the maximum tolerance level of 20 µgKg-1 aflatoxin B2. Out of the 440, 19.32 percent (n=85) were contaminated with OA. The occurrence of OA was found to be higher in maize (40%), sun flower (30%), wheat (28%), corn gluten (25%) and barley (24%). OA detected in rice, sorghum, peanut meal, soybean meal, guar meal, corn gluten and rice polish was found to be 20 percent. The findings further showed that maize had maximum mean OA concentration of 112.20 (+22.69) µgKg-1, followed by 59.43 (+22.32) µgKg-1 in wheat, 50.33 (+13.79) µgKg-1 in sunflower meal, 49.20 (+10.23) µgKg-1 in peanut meal and 39.14 (+ 15.06) µgKg-1  in rice polishing. Corn gluten meal, sorghum, barley, cotton seed meal and rapeseed meal contained mean OA concentration ranging from 30 to 36 µgKg-1. The OA content ranging from 10 to16.67 µgKg-1 was detected in samples of wheat bran, fish meal, blood meal and meat meal. The aflatoxin B2 and OA contamination of poultry feeds and feed ingredients having deleterious effects seems to pose a serious threat for local poultry farming sector which calls for regular testing and surveillance of poultry feeds and adoption of necessary remedial measures.
Keywords: Poultry feeds; feed ingredients; aflatoxin B2; Ochratoxin A